How does serum brain natriuretic peptide level change under nasal continuous positive airway pressure in obstructive sleep apnea-hypopnea syndrome?. Issue 1 (1st January 2016) - Msaad, Sameh; Marrakchi, Rim; Grati, Malek; Gargouri, Rahma; Kammoun, Samy; Jammoussi, Kamel; Yangui, Ilhem
Abstract : Background: Obstructive sleep apnea-hypopnea syndrome (OSAHS) is associated with cardiovascular morbidity and mortality, which can be improved by using continuous positive airway pressure (CPAP) therapy. However, the pathophysiological links between the two kinds of disease and the mechanism of the CPAP effect remain incompletely understood. We aimed to inquire into the myocardial involvement in this relationship. We suggested that serum brain natriuretic peptide (BNP) is sensitive enough to detect myocardial stress caused by OSAHS. Design and methods: Sixty-four subjects without cardiovascular disease (21 controls, 24 normotensive OSAHS patients, and 19 hypertensive OSAHS patients) were analyzed for serum BNP at baseline and serially over 6 months. CPAP was applied to 23 patients with severe OSAHS. Results: At baseline, the serum BNP levels were significantly higher ( p =0.0001) in the OSAHS group (22.3±14.79 pg/ml) than in the control group (9.2±6.75 pg/ml). Increased serum BNP levels were significantly associated with mean transcutaneous oxygen saturation (SpO2 ) ( p <0.0001), minimal SpO2 ( p =0.002), oxygen desaturation index ( p =0.001), and total sleep time spent with SpO2 lower than 90% ( p =0.002). All patients with elevated BNP levels (≥37 pg/ml) had moderate or severe OSAHS (11/43 OSAHS patients). The more severe the OSAHS, the higher the BNP levels were. However, only the difference between severe and mild OSAHS was statistically significant ( p =0.029). Hypertensive OSAHS patients had the highest baseline BNP levels (27.7±16.74 pg/ml). They were significantly higher ( p =0.001) than in normotensive OSAHS patients (18±11.72 pg/ml) ( p =0.039) and the controls (9.2±6.75 pg/ml). As compared with baseline, treatment with CPAP significantly decreased BNP levels in both hypertensive and normotensive OSAHS patients (respectively, from 36±16.10 to 29.7±14.29 pg/ml, p <0.001, and from 20±10.09 to 16±8.98 pg/ml, p <0.001). In contrast, the BNP levels slightly increased in the controls (from 9.2±6.75 to 9.5±7.02 pg/ml, p =0.029), but there was no statistically significant difference in comparison with the baseline value. The effect of CPAP on BNP levels was more marked in patients with higher baseline BNP levels and those with the most prolonged nocturnal desaturation ( p =0.001, r= 0.65). It was also more marked in hypertensive OSHAS patients ( p =0.015, r =0.72) in comparison with normotensive OSAHS patients ( p =0.03, r =0.62). Conclusion: BNP seems to be sensitive enough to detect myocardial stress caused by OSAHS. As such, it is a potential marker for screening of preclinical cardiovascular damage in patients with untreated OSAHS. Application of CPAP decreases levels significantly in normotensive and particularly in hypertensive OSAHS. These findings are consistent with previous results suggesting the potential benefits of CPAP on cardiovascular outcome in OSAHS patients.